Comprehensive molecular characterization of the transcriptome of HCC patients - Lee, CG (NATURE PUBLISHING GROUP, 2022)
51st Conference of the European-Society-of-Human-Genetics (ESHG) in conjunction with the European Meeting on Psychosocial Aspects of Genetics (EMPAG)